2018
DOI: 10.1088/1361-6595/aada9e
|View full text |Cite
|
Sign up to set email alerts
|

Phase-resolved optical emission spectroscopy of a transient plasma created by a low-pressure dielectric barrier discharge jet

Abstract: A transient plasma created by a low-pressure dielectric-barrier discharge operated with argon was investigated by means of optical emission spectroscopy and imaging. Images of the discharge and emission spectra were recorded with sub-phase resolution and relative densities of excited argon states were obtained. Profiles of densities and electron temperatures were evaluated for the discharge cycle by comparison with results of a collisional-radiative model (CRM). To overcome difficulties in sub-cycle modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…For each individual transition the self-absorption factor was calculated by (5) and (6). The characteristic absorption length of 2 mm was used due to the high aspect ratio of the discharge geometry [18] resulting in satisfactory estimations as shown in our previous work [12].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For each individual transition the self-absorption factor was calculated by (5) and (6). The characteristic absorption length of 2 mm was used due to the high aspect ratio of the discharge geometry [18] resulting in satisfactory estimations as shown in our previous work [12].…”
Section: Resultsmentioning
confidence: 96%
“…It was found that splitting of energetic levels in the presence of magnetic field will effect the self-absorption properties by increasing transparency of the system. The measurements were done on an example of low pressure transient plasma conditions, previously investigated in [12], where phase resolved 1s magnetic sub-level densities were evaluated for wider electron temperature and density range in the presence of an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…5. Emission spectra of an argon low temperature plasma have been successfully analysed by modelling collisional and radiative processes responsible for the population of excited states [43,44]. In the complete model for argon [44,45] the populations of the first 14 excited states (Ar(1s) and Ar(2p) branches) were modelled including electron impact excitation from ground state, electron coupling between and within the Ar(1s) and Ar(2p) levels, and electron quenching and radiative processes including light trapping.…”
Section: B Collisional Radiative Model Of An Argon Discharge Containing Aluminiummentioning
confidence: 99%
“…Emission spectra of an argon low temperature plasma have been successfully analysed by modelling collisional and radiative processes responsible for the population of excited states [43,44]. In the complete model for argon [44,45] the populations of the first 14 excited states (Ar(1s) and Ar(2p) branches) were modelled including electron impact excitation from ground state, electron coupling between and within the Ar(1s) and Ar(2p) levels, and electron quenching and radiative processes including light trapping. It was shown that in the case of low temperature plasmas with moderate electron densities and temperatures, the collisional-radiative model (CRM) can be simplified to an extended corona model including excitation from ground and 1s states and radiation transfer processes [44,46].…”
Section: B Collisional Radiative Model Of An Argon Discharge Containing Aluminiummentioning
confidence: 99%
See 1 more Smart Citation